Interactive Effects of Filamentous Fungi and Cucurbitacin Phytonematicide on Growth of Cowpea and Suppression of Meloidogyne enterolobii - Pofu, Kgabo Martha; Mashela, Phatu William (Frontiers in Microbiology, 2022)
Cowpea [(Vigna unguiculata (L.) Walp)] is highly susceptible to the emerging guava root-knot nematode, Meloidogyne enterolobii, with available management options being limited due to the withdrawal of effective fumigant nematicides from the agrochemical markets. Filamentous fungi, available as Biocult (a.i. Glomus species + Trichoderma asperellum Lieckf and Nirenberg) and Nemafric-BL phytonematicide (a.i. cucurbitacin B) each improves plant growth and suppresses nematode population densities. However, when filamentous fungi like Biocult are combined with other biocontrol agents, the combined effects either have synergestic or antagonistic effects on the test variables. The combined effects of Biocult and cucurbitacin phytonematicides on plant growth and nematode suppression remain undocumented. The objective of this study was therefore to determine the combined effects of Biocult and Nemafric-BL phytonematicide on growth of cowpea var. Eureka and suppression of M. enterolobii population densities. Eureka was subjected to the effects of the two products in a 2 × 2 factorial experiment on a field infested with M. enterolobii. At harvest, the interaction of Biocult and Nemafric-BL phytonematicide was highly significant (P ≤ 0.01) on plant and nematode variables, with a two-way table used to assess the findings. Relative to untreated control, Biocult alone increased plant growth variables from 15 to 74%. Similarly, NemafricBL phytonematicide increased plant variables from 14 to 61%, whereas the combined effects significantly increased dry shoot mass (19%) and dry harvestable leaf mass (21%), but did not have significant effects on plant height and stem diameter. Relative to untreated control, Biocult alone reduced nematode eggs in root (80%), J2 in root (84%) and J2 in soil (53%), whereas the combined relative effects of the two products did not have significant effects on nematode population densities. In conclusion, Biocult and Nemafric-BL phytonematicide had antagonistic effects on growth of cowpea and suppression of M. enterolobii population densities and therefore, should be used separately in cowpea production.